2023
DOI: 10.1021/acssynbio.2c00587
|View full text |Cite
|
Sign up to set email alerts
|

Receptor Elimination by E3 Ubiquitin Ligase Recruitment (REULR): A Targeted Protein Degradation Toolbox

Abstract: In recent years, targeted protein degradation (TPD) of plasma membrane proteins by hijacking the ubiquitin proteasome system (UPS) or the lysosomal pathway has emerged as a novel therapeutic avenue in drug development to address and inhibit canonically difficult targets. While TPD strategies have been successful in targeting cell surface receptors, these approaches are limited by the availability of suitable binders to generate heterobifunctional molecules. Here, we present the development of a nanobody (VHH)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…The TPD systems involving either ASGR or ZNRF3/RNF43 E3-ligases include, LYTAC containing an ASGR specific ligand fused to an antibody against a POI (protein of interest, Ahn et al, 2021); and AbTAC (Cotton et al, 2021), PROTAB (Marei et al, 2022), or REULR (Siepe et al, 2023), which are bispecific antibodies that bring E3 ligases to the proximity of a POI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The TPD systems involving either ASGR or ZNRF3/RNF43 E3-ligases include, LYTAC containing an ASGR specific ligand fused to an antibody against a POI (protein of interest, Ahn et al, 2021); and AbTAC (Cotton et al, 2021), PROTAB (Marei et al, 2022), or REULR (Siepe et al, 2023), which are bispecific antibodies that bring E3 ligases to the proximity of a POI.…”
Section: Discussionmentioning
confidence: 99%
“…6). Therefore, from the perspective of enhanced ASGR1 degradation, the SWEETS molecules also have what are now described as AbTAC (Cotton et al, 2021), PROTAB (Marei et al, 2022), REULR (Siepe et al, 2023), and ROTAC (Sun et al, 2023) TPD activities. This E3-mediated degradation is an efficient and rapid process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antibody-based targeting of E3 ligases and ASGR1 have been found to facilitate proteasomal degradation via ubiquitylation or lysosomal pathway degradation. 32 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 These studies have demonstrated the feasibility of cell-targeted RSPO mimetics and enabled new opportunities for the development of RSPO mimetic WNT modulators for regenerative medicine.…”
Section: Novel Wnt-activating Approachesmentioning
confidence: 94%
“…A bispecific nanobody-based degrader modality was also recently reported, named REULR (receptor elimination by E3 ubiquitin ligase recruitment) (Figure 3). [28] Nanobodies are single-chain variable domain antibodies, and thus REULRs are smaller than AbTACs and PROTABs, which can offer practical and potentially pharmacokinetic advantages. Synthetic nanobodies generated against the extracellular domains of a series of RNF ligases were combined with two known EGFR nanobodies.…”
Section: Antibody-based Protacs (Abtacs) Proteolysis Targeting Antibo...mentioning
confidence: 99%